The complete chloroplast genome of Hibiscus syriacus using long-read sequencing: Comparative analysis to examine the evolution of the tribe Hibisceae - Koo, Hyunjin; Shin, Ah-Young; Hong, Seongmin; Kim, Yong-Min (Frontiers in Plant Science, 2023)
Hibiscus syriacus, a member of the tribe Hibisceae, is considered an important ornamental and medicinal plant in east Asian countries. Here, we sequenced and assembled the complete chloroplast genome of H. syriacus var. Baekdansim using the PacBio long-read sequencing platform. A quadripartite structure with 161,026 base pairs was obtained, consisting of a pair of inverted repeats (IRA and IRB) with 25,745 base pairs, separated by a large single-copy region of 89,705 base pairs and a short single-copy region of 19,831 base pairs. This chloroplast genome had 79 protein-coding genes, 30 transfer RNA genes, 4 ribosomal RNA genes, and 109 simple sequence repeat regions. Among them, ndhD and rpoC1, containing traces of RNA-editing events associated with adaptive evolution, were identified by analysis of putative RNA-editing sites. Codon usage analysis revealed a preference for A/U-terminated codons. Furthermore, the codon usage pattern had a clustering tendency similar to that of the phylogenetic analysis of the tribe Hibisceae. This study provides clues for understanding the relationships and refining the taxonomy of the tribe Hibisceae.